Helicobacter pylori and oral pathology: Relationship with the gastric infection - Adler, Lidia Isabel (2014)
Helicobacter pylori (Hp) has been found in the oral cavity and stomach, and its infection is one of the most frequent worldwide. We reviewed the literature and conducted a Topic Highlight, which identified studies reporting an association between Hp-infection in the oral cavity and Hp-positive stomach bacterium. This work was designed to determine whether Hp is the etiologic agent in periodontal disease, recurrent aphthous stomatitis (RAS), squamous cell carcinoma, burning and halitosis. Record selection focused on the highest quality studies and meta-analyses. We selected 48 articles reporting on the association between saliva and plaque and Hp-infection. In order to assess periodontal disease data, we included 12 clinical trials and 1 meta-analysis. We evaluated 13 published articles that addressed the potential association with RAS, and 6 with squamous cell carcinoma. Fourteen publications focused on our questions on burning and halitosis. There is a close relation between Hp infection in the oral cavity and the stomach. The mouth is the first extra-gastric reservoir. Regarding the role of Hp in the etiology of squamous cell carcinoma, no evidence is still available.